The effect of different nasal irrigation solutions following septoplasty and concha radiofrequency: a prospective randomized study - Kurtaran,Hanifi (2018)
Abstract Introduction Nasal irrigation solutions are widely used following endonasal surgery. These irrigation solutions remove infective debris and crusts, reducing the probability of synechia formation, and accelerate mucosal healing. Objective The aim of the present study was to compare the effects of nasal irrigation solutions with different contents following septoplasty and concha radiofrequency. Methods The present study was a prospective, randomized, controlled simple blind study of 120 patients who underwent septoplasty and bilateral concha radiofrequency. Patients were divided into four groups according to the nasal irrigation solution used: tap water, buffered isotonic saline, saline with xylitol, and hypertonic sea water. Patients were examined on the 7th and 15th postoperative days. A saccharine test was applied to determine mucociliary activity preoperatively and on the 7th and 15th postoperative days. Patients were asked about drying and obstruction using a 10 cm visual analog scale. In addition, patients were examined to determine the crusting score. Results There was no significant difference found in the preoperative and 7th and 15th postoperative days' mucociliary clearance times among the four groups. The crusting score was found to be significantly lower in the hypertonic sea water group (p < 0.001). Drying and obstruction on the 7th and 15th postoperative days were found to be significantly more comfortable in the hypertonic sea water group (p < 0.001). Conclusion Hypertonic sea water is the recommended irrigation solution, as it is associated with less crusting, drying, and obstruction in the nose for the postoperative period following septoplasty and concha radiofrequency.